Comparative Study of Architecture of the Great Mosque at Samarra, Iraq and Ibn Tulun Mosque at Cairo, Egypt - Zahid Tauqeer Ahmad; Seemin Aslam (Journal of Islamic Thought and Civilization, 2020)
Ever since the emergence of Islam, mosque has always been the most dominant feature in any Islamic built environment. Over the course of time, mosque architecture has gone through a process of various forms of uses and expressions in terms of its transformation. Its style, layout, building form, type of ornamentation used, building materials and construction technology usually provide vital information not only about the practice of Islam in general but also about the timeline, prevailing geopolitical environment, religious conviction, purpose, need and the region in which the mosque was built. This research paper emphasizes the study of the general characteristics of the two earliest examples of mosques in Islamic architecture through extensive literature review. It also highlights the historical and geopolitical context, built form, size, shape, configuration, color, texture, materials used, scale and type of decorative elements of the two most outstanding and heavily restored mosques to date.